Administrative and Organizational Mechanisms for the Spatial Development of Shrinking Cities - E. E. Plisetskii (Управленческие науки)
The problem of population decline, economic activity decrease and deterioration of investment attractiveness has become topical on the agenda of sustainable development of industrial or single-industry cities in most developed countries (uSA, Eu, Australia) during the last century. New urban trends are increasing of the economic efficiency of urban areas usage, encouraging restrain of the population, including youth and employable people, and attracting new ones through the creation of required jobs and the formation of comfortable living conditions. All of these demanded the mechanisms and tools development for the social and economic development of cities. world experience has accumulated various approaches to the transformation of shrinking cities —  economic and financial instruments supporting the development and provision of partnership of key stakeholders of cities, integrated urban development programs, tools for optimizing the spatial and territorial structure of cities, etc. The paper analyzes the existing practices of application of administrative and organizational mechanisms for the spatial development of shrinking cities in the united States, Britain, Germany, Spain and Australia. Based on the analysis, key conclusions are drawn about the factors that divide the trajectories from decline to the cities restoration. The practical significance of the conclusions lies in the possibility of using them in the development of strategies and programs for the russian cities development that are experiencing a tendency towards a contraction of economic and territorial space.